APLIKASI PEMESANAN ONLINE BUSANA MUSLIM PADA MADANI MUSLIM SEMARANG (Information Technology and Telematics, 2013)
Madani Muslim Semarang is one of the stores in Semarang are engaged in the sale muslim clothing and hijab. However, the system in place now, there are still many problems that occur both in the civil and in the Semarang Muslim consumers, especially those outside the city of Semarang. Semarang Madani Muslim party has not had a special media to promote its products and recording sales transactions reports are still done manually using only existing proof of the transaction and the consumer still had to come to the store if you want to get information on products and want to order products Moslem , and consumers should contact Madani Muslim Semarang via sms or phone if you want to know the progress of their reservation. System development methods used in this study is composed of Web Engineering formulation, planning, analysis, engineering, implementation. System design using OOD and creating a website using PHP programming and MySQL databaseKeywords : Order Online,PHP, MySQL